Vortex generation in stirred binary Bose-Einstein condensates - Da Silva, Anacé N. [UNESP]; Kumar, R. Kishor; Bradley, Ashton S.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2023)
Binary Bose-Einstein condensates of two distinct atomic species are studied, with interesting effects being verified due to the imbalance of atomic masses. We study the formation of vortices and associated turbulence flows created by stirring two mass-imbalanced coupled Bose-Einstein condensates in the miscible regime. We consider the mixture in the laboratory frame, confined in a pancake-like harmonic trap slightly perturbed elliptically by a time-dependent periodic potential, which introduces turbulent dynamics with final stable patterns of vortices, induced by the periodicity of the perturbation. Derived rotational frequencies are shown to be associated with the observed vortex patterns in the asymptotic regime, with a correspondence between the stirring procedure and a direct time-independent approach being indicated. It was also confirmed that a larger pattern of vortices is supported by the higher mass condensed species at the same frequency. For the experimentally accessible mixtures Rb85-Cs133 and Rb85-Rb87, we numerically solve the equations of motion and analyze the system dynamics using a range of measures including energy spectra. In the transient turbulent regime, spectral analysis shows evidence for the characteristic k-5/3 Kolmogorov classical law associated with turbulence, modified by the universal k-3 vortex core scaling in the ultraviolet regime.